A Conceptual Framework for Procurement Decision Making Model to Optimize Supplier Selection: The Case of Malaysian Construction Industry - Chuan N.M.; Thiruchelvam S.; Mustapha K.N.; Muda Z.C.; Husin N.M.; Yong L.C.; Ghazali A.; Rusli M.E.; Itam Z.B.; Beddu S.; Kamal N.L.M. (Institute of Physics Publishing, 2023)
Construction industry; Conceptual frameworks; Malaysian construction industry; metrics; procurement; Procurement decisions; Supplier selection; Supplier selection process; Systematic process; Decision making; conceptual framework; construction industry; decision making; econometrics; industrial development; industrial policy; infrastructure; optimization; research work; stakeholder; Malaysia